Implementasi Metode Pembelajaran Kitab Kuning di Dayah Mahyal Ulum Al-Aziziyah Untuk Meningkatkan Karakter Santri - Maulana, Muhaddis; Nur Kholis, M. Maulana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research analyzes the implementation of the yellow book learning method in Dayah Mahyal Ulum Al-Aziziyah, Greater Aceh, in the context of improving students' character. The yellow book as an Islamic classical text in Arabic form mumbled (without harakat) requires an effective learning method so that students can understand and apply Islamic values in their daily lives. This qualitative research with a case study approach uses observation techniques, in-depth interviews, and document analysis. The results of the study show that this dayah applies six main methods: bandongan (shared reading), boh bareh (giving harakat), surah (talk), niqasy (question and answer), muthala'ah (repeated reading), and nazam bait (composition of poetry). The implementation of these methods results in the improvement of students’ character in four aspects: writing ability (calligraphy and rigor), reading ability (fluency and pronunciation), meaning ability (text interpretation), and comprehension ability (application of Islamic values). The study concludes that the application of varied and contextual learning methods can significantly strengthen students’ character, thus recommended to be applied more widely in traditional Islamic educational institutions.